alg2trig

posted by .

2(3y-4)^(3/5)-4=50

  • alg2trig -

    2(3y-4)^(3/5) = 54
    (3y-4)^(3/5) = 27

    3y - 4 = 27^(5/3)
    3y = 27^(5/3) + 4
    y = (27^(5/3) + 4)/3
    = (243 + 4)/3 = 247/3 or 82 1/3

  • alg2trig -

    1-(1/a)/1-(1/a^2)

  • alg2trig -

    multiply top and bottom by a^2 to get

    (a^2-a)/(a^2-1)
    = a(a-1)/(a+1)(a-1)
    = a/(a+1)

    or, since you seem to like reciprocals so much,

    1 /(1+1/a)

    :-)

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. math alg2trig

    how would you find the horizontal and vertical asymptote of y=x+2/x-3 and y=-3x+2/-4x-5?
  2. alg2trig

    16log4^1/64=x

More Similar Questions